Corporate governance, foreign direct investment, and bank income smoothing in African countries. Issue 4 (29th October 2019) - Pinto, Inês; Gaio, Cristina; Gonçalves, Tiago
Abstract : Purpose: The purpose of this paper is to investigate the role of corporate governance mechanisms and foreign direct investment (FDI) to restrain or stimulate the use of loan loss provisions (LLPs) by managers to smooth earnings in African banks. Design/methodology/approach: This study uses a sample of 112 listed and non-listed banks from 20 African countries, covering the period 2011–2017. Models are estimated using the pooled ordinary least squares regression, as well as Blundell and Bond (1998) system GMM. Findings: The results suggest that bank managers use LLPs to reduce income volatility and that ownership concentration increases income smoothing. The findings also show that FDI plays a fundamental role to restrain managerial discretion in developing countries, increasing corporate governance practices in the host country. Practical implications: These findings are relevant for banking regulators and supervisors in order to determine which corporate governance mechanisms can be used in developing countries to increase the quality of financial reporting. A policy model that promotes FDI boosts financial reporting transparency, contributing to greater financial markets development. Originality/value: The authors extend the existing literature on the influence of corporate governance mechanisms in limiting managerial discretion by focusing on the role that foreign shareholders may have in disciplining banks financial reporting quality in countries with weak institutional quality.